The M.D. Anderson surgical oncology handbook - Feig, Barry W., 1959-; Ching, C. Denise (Christine Denise) (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"The current edition of The Handbook provides an overview of current care of patients with cancer diagnoses commonly evaluated and treated by surgical oncologists, and in doing so continues to align such care with the underlying philosophy of the Department of Surgical Oncology at M.D. Anderson: multidisciplinary, cooperative care is the ideal way to manage patients with cancer. Such care begins with an understanding of the underlying tumor biology and natural history of the disease and includes technical excellence in the delivery of indicated surgical treatment. It also demands integration of essential information from the available literature on currently preferred treatment modalities, and emphasizes appropriate inclusion of adjunctive specialty care, including medical oncology, radiation oncology, interventional radiology, palliative care, pain management, physical therapy, nutritional support, social services and nursing"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cancer -- Surgery -- Handbooks, manuals, etc; Electronic books